Investigation of the Protective Effects of Epigallocatechin-3-Gallate against Cisplatin-Induced Testicular Toxicity in Rats by Bax/Bcl-2, TNF-? and NF-KB Signaling Pathways - Ozdemir, Ilkay; Beyaz, Seda; Erman, Orhan; Ozercan, Ibrahim Hanifi; Celayir, Nasrullah; Temizkan, Nuray; Aslan, Abdullah (Inst Tecnologia Parana, 2026)
A good source of polifenol that has anti-inflammatory, antimutagenic, and anti-oxidative properties is Epigallocatechin-3-Gallate (EGCG), which has been used for many years as a medicinal supplement. As with other tissues, it has been demonstrated that EGCG significantly protects testicular tissue and inhibits the development of tumors in cancer cells. It was investigated if the polyphenolic catechin EGCG, which has antioxidant and anticarcinogenic properties, had any protective effects against the cisplatin-induced testicular toxicity. 28 male rats were separated into 4 groups for this investigation. Western blotting was used to measure the expression of the proteins Bax, Bcl-2, TNF-alpha and NF-kappa B. Testicular tissue was also histopathologically examined, and the results were statistically analyzed. As a result, while malondialdehyde (MDA) decreased, glutathione (GSH) levels and catalase (CAT) activity were increased in rat groups that were administered EGCG, which has therapeutic properties in testicular tissue. When compared to the cisplatin (Cis) group, it was shown that the expression levels of proteins that are markers of inflammation were much lower in the EGCG group (EGCG+Cis). In the histological investigation, it was shown that the
Keywords: Egcg; Damage; Injury; Bcl-2; Bax